2005
DOI: 10.1089/jpm.2005.8.96
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors Associated with Better Quality of Life for Older Bereaved Persons

Abstract: Background: Bereavement is a risk factor for declines in health, adverse health behaviors, increased physician visits, and mortality, and occurs with greatest frequency in later life. Little is known about health behaviors that are associated with better quality of life among recently bereaved older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
0
40
1
2
Order By: Relevance
“…Maintaining regular physical activity was found to provide benefits including protection from decreased physical function especially in the lower limbs ( tables 1 and 2 ). Other studies also found that exercise predicted a better self-rated health, physical functioning, fewer physical role limitations, and greater energy in elderly bereaved persons [44] ; exercising is predictive of fewer IADL limitations, greater longevity, positive affect, and meaning in life 8 years later among the old old [45] , and during a comprehensive rehabilitation program in chronically ill elderly. Similarly to our findings, Brach et al [46] found in a cross-sectional study that lower extremity performance was positively related to physical activity; inactive elderly individuals are most likely to have impaired performance.…”
Section: Discussionmentioning
confidence: 91%
“…Maintaining regular physical activity was found to provide benefits including protection from decreased physical function especially in the lower limbs ( tables 1 and 2 ). Other studies also found that exercise predicted a better self-rated health, physical functioning, fewer physical role limitations, and greater energy in elderly bereaved persons [44] ; exercising is predictive of fewer IADL limitations, greater longevity, positive affect, and meaning in life 8 years later among the old old [45] , and during a comprehensive rehabilitation program in chronically ill elderly. Similarly to our findings, Brach et al [46] found in a cross-sectional study that lower extremity performance was positively related to physical activity; inactive elderly individuals are most likely to have impaired performance.…”
Section: Discussionmentioning
confidence: 91%
“…One study with recently bereaved older individuals indicated that healthy behaviors, such as consistent exercise, monitoring caloric intake, and proper amount of sleep at 6-and 11-months postloss, were related to better QOL at 19-months postloss. 134 Among recently bereaved adults (average, 6 months postloss), greater use of religious/spiritual coping was associated with more functional disabilities and fewer outpatient physical healthcare visits at baseline but was not related to health status at the 4-month follow-up. 135 Identifying particularly vulnerable family caregivers before the relative's death based on the presence of a dysfunctional family system 136,137 and the demographic characteristics mentioned above has helped in interventions to prevent these caregivers from experiencing severe levels of grief and bereavement symptoms at 4 months, 130 6 months, 138 and 12 months after the loss.…”
Section: Family Caregivers' Qol At the Bereavement Phasementioning
confidence: 90%
“…The measure has been used in a variety of populations experiencing chronic pain or physical ill health. 9 Only the physical functioning scale was used in the present analysis. This reflects an individual's reported limitations relating to the demands of pain or illness.…”
Section: Maternal Questionnairesmentioning
confidence: 99%